Fast quantitative microwave imaging with resolvent kernel extracted from measurements. (20th March 2015) - Tu, S; McCombe, J J; Shumakov, D S; Nikolova, N K
Abstract: A quantitative imaging method is proposed based on microwave measurements where a direct inversion in real space is employed. The electrical properties of penetrable objects are reconstructed using a resolvent kernel in the forward model, which is extracted from calibration measurements. These measurements are performed on two known objects: the reference object (RO) representing the scatterer-free measurement and the calibration object representing a small scatterer embedded in the RO. Since the method does not need analytical or numerical approximations of the forward model, it is particularly valuable in short-range imaging, where analytical models of the incident field do not exist while the fidelity of the simulation models is often inadequate. The experimentally determined resolvent kernel inherently includes the particulars of the measurement setup, including all transmitting and receiving antennas. The inversion is fast, allowing for quasi-real-time image reconstruction. The proposed technique is demonstrated and validated through examples using simulated and experimental data. Its performance with noisy data is also examined. The concept of experimentally determined resolvent kernel in the forward model may be valuable in other imaging modalities such as ultrasound, photonic imaging, electrical-impedance tomography, etc.